Olapade, K. E. (2024)
Mathematics forms the bedrock of cognitive development for students logical reasoning and problem-solving abilities. However, the high failure rate among students in the subject remains a significant concern. Previous studies on students’ achievement in mathematics concentrated more on cooperative-based interventions than on game-based strategy using sudoku puzzles. Therefore, this study investigated the effects of sudoku puzzles on primary school pupils’ learning achievement in mathematics in Oyo state, Nigeria. It also examined the moderating effect of gender on dependent measures. The pretest-posttest control group quasi-experimental design with a 2x2 factorial matrix was utilised. The instruments used were the Pupils Mathematics Achievement Test (r=0.76) and the Teachers’ Instructional Guides. The treatment lasted six weeks. Data was analysed using Analysis of covariance and Scheffe post-hoc analysis at p<0.05. There was a significant two-way interaction effect of treatment and gender on pupils’ achievement in mathematics (F1,109) =28.89, partial η2=0.042). Although, the boys (19.67) benefited more from the treatment package than the girls (19.12), it was not significant. There were no significant main of treatment on pupils’ achievement. Sudoku puzzles instructional strategy improved pupils’ achievement in mathematics in Oyo state, Nigeria. Mathematics teachers in primary schools should adopt sudoku in teaching mathematics.